Pharmacovigilance-related events, disease burden and overall efficiency of care in european countries, 1990-2021 - Yin, Lin; Lin, Shuzhi; Liu, Qian; Zhu, Xiaoying; Liu, Wei; Shen, Yifang; Li, Zimeng; Feng, Bianling (Frontiers in Pharmacology, 2025)
ObjectivesThis study aimed to evaluate and compare the disease burden of pharmacovigilance-related events in European countries, to identify the factors related to pharmacovigilance-related inputs in various countries, and to analyze and compare the comprehensive benefits of pharmacovigilance-related events in various countries.MethodsUsing the Global Burden of Disease Study 2021 database, we combined information on adverse effects of medical treatment and drug use disorders to identify all pharmacovigilance-related events. We used principal component analysis to synthesize six first-level indicators to compare the burden of disease in each country in each year. We used data envelopment analysis to compare the efficiency of pharmacovigilance in each country.ResultsIn 2021, the Quality of care index for pharmacovigilance-related events was highest in Northern and Western European countries. Looking at data from 1990 to 2021, the change node of this index in most countries occurred around 2000 to 2010, and the value changed steadily. Countries with relatively low investment in health resources and less experience in the supervision of adverse drug reactions have higher comprehensive benefits of nursing for pharmacovigilance-related events.ConclusionThe effect of the development of a system for pharmacovigilance has a hysteresis. The disease burden is affected by various factors such as population aging, human resource investment, and medical and health needs, and the policy is highly dominant.